Synthesis of Bismuth-based Nanocomposites for Photocatalytic Degradation of Pollutants - Aashna (My University, 2022)
This thesis contains six chapters. The first chapter provides a brief introduction to hazardous pollutants and advanced oxidation processes such as semiconductor photocatalysis for the removal of pollutants from toxic water. The second chapter includes the synthesis of β-Bi2O3/BiOCl nanoflower for the photocatalytic degradation of methylene blue and fipronil. The third chapter summarizes the synthesis of β-Bi2O3/g-C3N4 nanosheets for the photocatalytic removal of methylene blue and fipronil. The fourth chapter elaborates on the designing of a ternary catalyst g-C3N4/Ag/BiVO4 where Ag nanoparticles act as electron shuttle and BiVO4/Ag has been fixated on the surface of g-C3N4 for the photodegradation of methylene blue and fipronil. The fifth chapter presents a tablet-like Bi3TaO7/BiOCl for the photocatalytic removal of methylene blue and tetracycline. The sixth chapter presents a ternary nanoflower-like Bi3TaO7/Ag/BiVO4 for the photodegradation of methylene blue and tetracycline.
Keywords: Nanocomposites; Bismuth; Photocatalytic; Organic Pollutants; Visible-Light